PENERAPAN TEKNOLOGI PENGOLAHAN TALAS KIMPUL MENJADI MIE INSTAN SEHAT - Putra, I.G.A.M.; Wiadnyani, A.A.I.S.; Putra, I.N.K. (Buletin Udayana Mengabdi; Vol 23 No 5 (2024): Buletin Udayana MengabdiDO - 10.24843/BUM.2024.v23.i05.p03, 2023)
Sanda Village is one of the villages located in Pupuan District, Tabanan Regency. The potential of this village is cocoyam and it has not been cultivated optimally. Cocoyam in Sanda Village has promising potential but has not been utilized optimally. The purpose of this community service is to synergize between the Women Farmer Group (KWT) and the Family Welfare Development Group (PKK) in Sanda Village and provide education, especially about the diversification of cocoyam flour processing into healthy instant noodles rich in fiber and antioxidants so that it can be used as an alternative in develop the potential of community in entrepreneurship. This service method is training and mentoring in terms of processing cocoyam into products with economic value accompanied by good packaging and labeling. The results achieved from this community service activity are the creation of food product innovations in the form of healthy instant noodles rich in fiber and antioxidants. Keywords: Processing, Cocoyam, Healthy Noodles, Sanda,Tabanan